A Novel Reservation and Allocation Approach of Shared Parking Slots considering the Noncritical Aisle Space - Ke Huang; Shaozhi Hong; Zhiyuan Shi; Haoran Jiang (Journal of Advanced Transportation)
Urban areas are experiencing a substantial increase in parking demand, which creates an imbalance due to the limited availability of parking facilities. To address this issue, effective parking management is necessary. Shared parking is an alternative solution that utilizes private plots which are vacant during the day to serve the parking needs of users engaged in nearby activities. While current parking management approaches have achieved high utilization rates for available parking slots, the use of aisle space in parking lots can alleviate oversaturated parking demands, especially during peak periods, for users with relatively short parking durations. This study aims to model the noncritical aisle space with time-space constraints in the shared parking slot allocation problem. We propose a programming model that maximizes the profit of the platform based on a reservation and allocation platform. Numerical experiments demonstrate that utilizing the aisle space can enhance the revenue and enable the platform to accommodate more requests that meet the requirements. Moreover, the presence of aisle parking slots may potentially result in slightly lower turnover rates of normal parking slots.